Modelling child persona for social behaviours in social network sites / Noor Hidayah Azmi - Azmi, Noor Hidayah (Institute of Graduate Studies, UiTM, 2018)
Children are becoming dependent on social network sites (SNS) to gratify their social needs. They are increasingly becoming users of SNS and emerging as an important user group. Despite much literature on children, not much is known about the social behaviour of the children when they gain access to SNS. It is due to limited access to children due to policy, legal or ethical reasons. This research identified children social behaviour to understand how they behave in SNS. Subsequent to this, a child persona was modelled to represent children as a social networker. The creation of persona involved three steps, including collecting user data, segmenting data into groups and transferring data into persona. In user research, qualitative approach was carried out through self-reporting method such as cultural probes and interviews. It involved seven children between the ages of 10-12 years old. The initial phase in user research involved designing children's probes for capturing social behaviour. Then, the research conducted a contextual data collection in situ and over time, as part of children's daily life. The findings showed that the probes approach can be a potential method for children to self-report their social behaviour related to SNS…